Comparison of Two Rapid Diagnostic Assays for Detection of Immunoglobulin M Antibodies to Dengue Virus - Wu, Shuenn-Jue L. (American Society for Microbiology, 2000)
Two easy-to-use commercial diagnostic assays, a dipstick enzyme-linked immunosorbent assay (ELISA) (Integrated Diagnostics, Baltimore, Md.) and an immunochromatographic card assay (PanBio, Brisbane, Australia) were evaluated for detection of immunoglobulin M (IgM) antibody to dengue virus with an in-house IgM antibody capture microplate ELISA as a reference assay. The dipstick ELISA was based on the indirect-ELISA format using dengue 2 virus as the only antigen and enzyme-labeled goat anti-human IgM antibody as the detector. The total assay time was 75 min. The immunochromatographic card assay was based on the antibody capture format and separately measured both anti-dengue virus IgM and IgG in the same test. Colloidal-gold-labeled anti-dengue virus monoclonal antibody bound with dengue virus 1 to 4 antigen cocktail was the detector, and anti-human IgM and IgG were the capture antibodies. The total assay time was <10 min. Sera from 164 individuals classified as either anti-dengue virus IgM positive (94) or anti-dengue virus IgM negative (70) in the reference microplate ELISA with a dengue virus 1 to 4 antigen cocktail were tested in the two commercial assays. The dipstick ELISA missed 7 of 94 positive samples, for a sensitivity of 92.6%, while the immunochromatographic card assay missed two positive samples, for a sensitivity of 97.9%. Of the 70 negative samples, four were false positive by the dipstick ELISA and two were false positive in the immunochromatographic card assay, resulting in specificities of 94.3 and 97.1%, respectively. Both commercial assays provide sensitive and specific detection of anti-dengue virus IgM antibody and could prove useful in settings where the microplate ELISA is impractical.